The QIBA Profile for FDG PET/CT as an Imaging Biomarker Measuring Response to Cancer Therapy - Kinahan, Paul E. (Radiology, 2020)
The Quantitative Imaging Biomarkers Alliance (QIBA) Profile for fluorodeoxyglucose (FDG) PET/CT imaging was created by QIBA to both characterize and reduce the variability of standardized uptake values (SUVs). The Profile provides two complementary claims on the precision of SUV measurements. First, tumor glycolytic activity as reflected by the maximum SUV (SUV(max)) is measurable from FDG PET/CT with a within-subject coefficient of variation of 10%–12%. Second, a measured increase in SUV(max) of 39% or more, or a decrease of 28% or more, indicates that a true change has occurred with 95% confidence. Two applicable use cases are clinical trials and following individual patients in clinical practice. Other components of the Profile address the protocols and conformance standards considered necessary to achieve the performance claim. The Profile is intended for use by a broad audience; applications can range from discovery science through clinical trials to clinical practice. The goal of this report is to provide a rationale and overview of the FDG PET/CT Profile claims as well as its context, and to outline future needs and potential developments. © RSNA, 2020 Online supplemental material is available for this article. See also the editorial by Ulaner in this issue.